Comparative antidiarrheal and antiulcer effect of the aqueous and ethanolic stem bark extracts of Tinospora cordifolia in rats - Mohanjit Kaur; Amarjeet Singh; Bimlesh Kumar (Wolters Kluwer Medknow Publications, 2014)
Tinospora cordifolia is indigenous to the tropical areas of India, Myanmar and Sri Lanka. The use of plant as remedy for diarrhea and ulcer is well-documented in Ayurvedic system of medicine. However, pharmacological evidence does not exist to substantiate its therapeutic efficacy for the same. The aim was to investigate the antidiarrheal and antiulcer activity of ethanolic and aqueous extracts of T. cordifolia in rats. The antidiarrheal activity of T. cordifolia extracts was evaluated by castor oil and magnesium sulfate-induced diarrhea using parameters such as onset of diarrhea, number of wet stools, total number of stool and weight of total number of stools. The antiulcer activity of extracts was investigated using ethanol and pylorus ligation-induced ulcer. Furthermore, tissue antioxidant parameters such as reduced glutathione, catalase activity and lipid peroxidation level were also investigated. Tinospora cordifolia extracts were more efficacious in reducing number of total stools in both the models of diarrhea and showed a dose-dependent antidiarrheal effect. The antiulcer activity of the extracts was confirmed by a reduction in ulcer index along with the decrease in gastric volume, total acidity, and an increase in pH of gastric content in both the models. The obtained results have established a pharmacological evidence for the folkloric use of the T. cordifolia as antidiarrhoeal and antiulcer agent.